2014
DOI: 10.5543/tkda.2014.36089
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of melatonin on adriamycin-induced cardiotoxicity in rats

Abstract: Melatonin has a protective effect on the heart against adriamycin-induced cardiotoxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…In an earlier research, it was proposed that doxorubicin raised MDA level (28). In our fi ndings, a reduction in activities of SOD, GPx and CAT in the adriamycin-induced group may have taken place because of improved generation of ROS such as superoxide and hydrogen peroxide which in turn bring about antioxidant enzymes inhibition (29). The treatment with pravastatin in part preserved the structural alterations resulting in morphology near to that of control group.…”
Section: Discussionmentioning
confidence: 55%
“…In an earlier research, it was proposed that doxorubicin raised MDA level (28). In our fi ndings, a reduction in activities of SOD, GPx and CAT in the adriamycin-induced group may have taken place because of improved generation of ROS such as superoxide and hydrogen peroxide which in turn bring about antioxidant enzymes inhibition (29). The treatment with pravastatin in part preserved the structural alterations resulting in morphology near to that of control group.…”
Section: Discussionmentioning
confidence: 55%
“…In the present study, melatonin had its improvement activity through various mechanisms including its antiapoptotic and antioxidants effects [11,12] to reduce the effects of free radicals. Furthermore, the concurrent treatment with melatonin might be led to inhibition of peroxidation of lipid.…”
Section: Discussionmentioning
confidence: 68%
“…The pineal gland is inactive in the day time but it is activated and starts to actively produce melatonin in the darkness. MEL participates in circadian rhythm regulation and has main role in anti aging processes [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…The level of HDL in the DOX‐NE group was significantly higher than that in the DOX‐Solution group. Bilginoğlu et al reported that the injection of DOX (at a cumulative dose of 18 mg/kg, i.p.) to Wistar‐albino rats on the 5th, 6th and 7th day elevated the level of TAG and decreased the HDL level.…”
Section: Discussionmentioning
confidence: 99%